Post-approval studies with the CFTR modulators Elexacaftor-Tezacaftor—Ivacaftor - Tümmler, Burkhard (Frontiers in Pharmacology, 2023)
Triple combination therapy with the CFTR modulators elexacaftor (ELX), tezacaftor (TEZ) and ivacaftor (IVA) has been qualified as a game changer in cystic fibrosis (CF). We provide an overview of the body of literature on ELX/TEZ/IVA published between November 2019 and January 2023 after approval by the regulators. Recombinant ELX/TEZ/IVA-bound Phe508del CFTR exhibits a wild type conformation in vitro, but in patient’s tissue a CFTR glyoisoform is synthesized that is distinct from the wild type and Phe508del isoforms. ELX/TEZ/IVA therapy improved the quality of life of people with CF in the real-life setting irrespective of their anthropometry and lung function at baseline. ELX/TEZ/IVA improved sinonasal and abdominal disease, lung function and morphology, airway microbiology and the basic defect of impaired epithelial chloride and bicarbonate transport. Pregnancy rates were increasing in women with CF. Side effects of mental status changes deserve particular attention in the future.